Use of iso‐osmolar contrast media during endovascular revascularization is associated with a lower incidence of major adverse renal, cardiac, or limb events. Issue 4 (12th November 2021) - Prasad, Anand; Amin, Amit P.; Ryan, Michael P.; Gunnarsson, Candace; Brilakis, Emmanouil S.
Abstract: Objective: We examined the association of iso‐osmolar contrast media (IOCM) versus low‐osmolar contrast media (LOCM) with major adverse renal, cardiovascular, or limb events in patients at high‐risk of acute kidney injury (AKI) undergoing peripheral endovascular procedures. Background: Procedural characteristics including iodinated contrast type and volume have been associated with adverse renal and cardiovascular outcomes in patients undergoing angiographic interventions. Methods: Patients at high‐risk of AKI, undergoing peripheral endovascular procedures were identified using the Premier Healthcare Database and separated into claudication and critical limb ischemia (CLI) cohorts. For each cohort, we compared IOCM versus LOCM for the primary endpoint of MARCE (major adverse renal or cardiovascular events) and secondary endpoints of major adverse renal events (MARE) and major adverse renal and limb events (MARLE). These outcomes were captured within the indexed hospitalization via adjusted multivariable regression analyses. Results: Two procedure‐based cohorts of high‐risk patients were formed: claudication ( N = 11, 976) and CLI ( N = 8713). Use of IOCM was associated with a significant absolute risk reduction (ARR) of 2.2% ( p < 0.0001) for MARCE overall and in each cohort (claudication, 1.8%, p = 0.0070; CLI, 2.7%, p = 0.0054). The incidence of MARE and MARLE in the overall cohort was also lower with the use of IOCM: MARE (ARR = 1.4%, p = 0.0072) and MARLE (ARR = 2.0%, p = 0.0043). Conclusions: Using IOCM versus LOCM in patients at high‐risk of adverse renal events undergoing peripheral endovascular procedures was independently associated with lower risk of MARCE, MARE, and MARLE.